Wearable Activity Technology And Action-Planning (WATAAP) to promote physical activity in cancer survivors: Randomised controlled trial protocol - Maxwell-Smith, C.; Cohen, P.; Platell, C.; Tan, P.; Levitt, M.; Salama, P.; Makin, G.; Tan, J.; Salfinger, S.; Kader Ali Mohan, G.; Kane, Robert; Hince, D.; et al. (2018)
© 2018 Asociación Española de Psicología Conductual Background/Objective: Colorectal and gynecologic cancer survivors are at cardiovascular risk due to comorbidities and sedentary behaviour, warranting a feasible intervention to increase physical activity. The Health Action Process Approach (HAPA) is a promising theoretical framework for health behaviour change, and wearable physical activity trackers offer a novel means of self-monitoring physical activity for cancer survivors. Method: Sixty-eight survivors of colorectal and gynecologic cancer will be randomised into 12-week intervention and control groups. Intervention group participants will receive: a Fitbit Alta™ to monitor physical activity, HAPA-based group sessions, booklet, and support phone-call. Participants in the control group will only receive the HAPA-based booklet. Physical activity (using accelerometers), blood pressure, BMI, and HAPA constructs will be assessed at baseline, 12-weeks (post-intervention) and 24-weeks (follow-up). Data analysis will use the Group x Time interaction from a General Linear Mixed Model analysis. Conclusions: Physical activity interventions that are acceptable and have robust theoretical underpinnings show promise for improving the health of cancer survivors.